Mature B-CELL neoplasms in Chernobyl clean-up workers of 1986–1987: summary of cytomorphological and immunocytochemical study in 25 years after Chernobyl accident - Gluzman, D.F.; Sklyarenko, L.M.; Nadgornaya, V.A.; Zavelevich, M.P. (Experimental Oncology, 2011)
The data on the verified cases of mature B-cell neoplasms (chronic lymphocytic leukemia – CLL, B-prolymphocytic leukemia, non-Hodgkin’s lymphoma in leukemization phase and multiple myeloma – MM; 146 cases in total) in the consecutive group of Ukrainian clean-up workers within 10–25 years after Chernobyl accident are summarized. B-cell neoplasms represent the most prevalent group among all diagnosed neoplasms of hematopoietic and lymphoid tissues in clean-up worker patients under study (49.4%). MM percentage in the patients of Chernobyl clean-up worker group turned out to be significantly higher than in the patients of the general populations studied at the same period. While the percentage of B-CLL is similar in clean-up worker patients and patients of general population, the trend towards younger age of patients with mature B-cell neoplasms in clean-up worker group is evident. The current concepts on the possible association between mature B-cell neoplasms (mainly B-CLL) and radiation exposure are briefly outlined. Only the precise diagnosis of hematopoietic malignancies combining with large-scale analytical epidemiological studies with careful dose assessment and long-term follow-up may represent the basis for resolving the question whether mature B-cell neoplasms may be radiogenic.